Nalar Ekologi Dalam Perspektif Islam - Saefullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
Problems of the environment now show an alarming rate. Various facts of environmental destruction on Earth have disturbed its inhabitants. This paper employs patterned library research and browsing to explore Islamic contributions in solving this problem. As a result, Islam gives great attention to various problems of human life, including environmental issues. This formulation is different from Western modernist scientific views that tend to rely only on technical approaches without considering other aspects. In fact, using a technical approach alone is not sufficient; it also requires other approaches, including the transcendent and the profane.